Genetic Gain in Yield and Associated Changes in Agronomic Traits in Wheat Cultivars Developed Between 1900 and 2016 for Irrigated Ecosystems of Northwestern Plain Zone of India - Yadav, Rajbir; Gupta, Soma; Gaikwad, Kiran B.; Bainsla, Naresh Kumar; Kumar, Manjeet; Babu, Prashanth; Ansari, Rihan; Dhar, Narain; Dharmateja, Palaparthi; Prasad, Rajender (Frontiers in Plant Science, 2021)
Knowledge about the yield gain over the years due to associated changes in the yield component traits is essential for a critical understanding of yield-limiting factors. To estimate genetic gain in grain yield of wheat varieties released between 1900 and 2016 for North-Western Plain Zone of India and to identify agronomic and/or genetic basis of the realized gains, two sets of wheat varieties comprising mega varieties and two recently developed varieties were evaluated under timely sown tilled and early sown conservation agriculture conditions respectively for 4 consecutive years. The average annual genetic gain in grain yield since 1905 under timely sown irrigated conditions was found to be 0.544% yr-1 over the average of all varieties and 0.822% yr-1 (24.27 kg ha-1 yr-1) over the first released variety, NP4. The realized mean yield increased from 2950 kg ha-1 of the variety NP 4 released in 1905 to 5649 kg ha-1 of HD 3086 released in 2014. Regression analysis revealed a linear reduction in height and peduncle length over the years with a simultaneous and linear increase in biomass at the rate of 43.9 kg ha-1 yr-1 or relatively at 0.368% yr-1 mainly because of delayed heading and increased crop duration. Regression analysis showed no trend for tiller number and thousand-grain weight. Harvest index (HI) though was found to linearly increase relatively at the rate of 0.198% per annum polynomial regression improved the fitness of data with indication of an increase in HI since 1982. Interestingly, genetic gain evaluation under early sown conservation agriculture conditions for four years showed similar relative gain (0.544%) but with a higher absolute value (29.28 kg ha-1 yr-1). Major mega varieties like Kalyan Sona, HD2009, PBW 343, HD2967, and HD3086, which occupied a comparatively larger area, were found highly plastic to the improvements in the production environment under timely sown conditions.